EXPLORING STUDENTS' ENGLISH LEARNING EXPERIENCES THROUGH GAME-BASED LEARNING: A PHENOMENOLOGICAL STUDY OF THE USE OF GIMKIT AT STAI SUSHA SIAK - Panduwinata, Tiara (Multidisciplinary Indonesian Center Journal (MICJO), 2025)
English language learning in Islamic colleges faces challenges related to motivation, engagement, and a classroom atmosphere that tends to be monotonous. In today's digital context, Game-Based Learning (GBL) offers an innovative approach that can change these dynamics through fun and interactive game elements. This study aims to explore the subjective experiences of students at the Susha Siak Islamic College (STAI) in using Gimkit as a game-based English learning medium. The approach used is interpretive phenomenology based on Heidegger's thinking, which focuses on the meaning of participants' life experiences. Data were obtained through in-depth interviews, participant observation, and reflective journals from seven students who actively used Gimkit in their English classes. Data analysis followed Colaizzi's (1978) steps to identify essential themes from the participants' experiences.The results of the study show three main themes: (1) fun and challenging learning, (2) a more lively and competitive classroom atmosphere, and (3) increased cohesiveness and solidarity among students. The learning experience through Gimkit brings out strong intrinsic motivation, self-confidence, and positive emotional involvement. This study concludes that GBL through Gimkit not only improves the effectiveness of English language learning, but also strengthens the values of togetherness and collaboration in the context of Islamic higher education.